Opening pupils' eyes to the Sun. Issue 6 (1st December 2020) - French, Ryan; James, Alexander; Baker, Deborah; Dunn, William; Matthews, Sarah; da Silva Pestana, Brian; Graham, Grace; Shackell, Benjamin; Carretero, Adam Smith; Trindade, Granger
Abstract : Ryan French and colleagues discuss their Hinode/EIS outreach work and the resulting resources available for A-level classes Abstract: Ryan French and colleagues discuss their Hinode/EIS outreach work and the resulting resources available for A-level classes.